Pengaruh Net Operating Margin dan Kualitas Aktiva Produktif terhadap Return on Asset di Bank BJB Syariah - Dwi Afrilla Nur Parisa; Mario Aldo Triadi Abidin (Ma'soem University, 2022)
Based on the results of the study, the background of this research is the gap between theory and practice between NOM and KAP on ROA at Bank BJB Syariah for the period 2017-2021. This study aims to determine how the influence of NOM and KAP on ROA at Bank BJB Syariah either partially or simultaneously. The object of research in this thesis is the financial statements of Bank BJB Syariah in 2017-2021. The type of research is quantitative associative, with secondary data types and uses data collection techniques in the form of documentation and literature study. While the population in this study are all financial statements of Bank BJB Syariah for the period 2017-2021. The sample in this study is the financial ratio report of Bank BJB Syariah totaling 5 financial statements. The results showed that there was a significant effect between NOM on ROA at BJB Syariah Bank with the results of the t test where the value of tcount > ttable (19.382 > 2.35)., there was no significant effect between KAP on ROA at BJB Syariah Bank with the test results t where tcount < ttable (0.480 < 2.35), and simultaneously there is no significant effect between NOM and KAP on ROA at BJB Syariah Bank with F test results where Fcount < Ftable (-1.719 < 19.16).